HUBUNGAN ANTARA SPIRITUALITAS DAN STRES PADA MAHASISWA YANG MENGERJAKAN SKRIPSI - Damar Aditama (EL-TARBAWI, 2017)
This research aims to determine the relationship between spirituality and stress on college student who work on the final project. Subjects in this study are Islamic college student and are working on the final project at least one semester or six months. Characteristics subject is men and women from the age of 20- 27 years, amounting to 82 people. Hypothesis proposed in this research is there is a negative relationship between spirituality with stress on college student who work on the final project. The higher the spirituality the lower the stress, the lower the spirituality the higher the stress. The data collected in this study used two measuring tools given on the subject, ie stress scale on thesis based on Sarafino scale theory (Permana, 2009) and Spirituality Orientation Inventory (SOI) compiled by Wahyuningsih (2009) and refers to Elkins theory.This research uses parametric analysis technique of product moment from Pearson. The analysis of this research showed results (r) -0.338 and p = 0.001 (p <0.01). These results indicate a negative relationship between spirituality with the stress of college student who are working on thesis. The higher the spirituality the lower the thesis stress on the college student, the lower the spirituality the higher the thesis stress on the college student. Thus, the hypothesis is accepted Keywords: College Student, Thesis, Spirituality, Stress